2004
DOI: 10.2119/2004-00045.bischoff
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Imprinting of IGF2 Is Maintained in Infantile Hemangioma despite its High Level of Expression

Abstract: Hemangioma, the most common tumor of infancy, is characterized by rapid growth and slow regression. Increased mRNA expression of insulin-like growth factor 2 (IGF2) has been detected in the proliferating phase by cDNA microarray analysis, but the underlying mechanism causing the increase remains unknown. Here, using quantitative real-time polymerase chain reaction (PCR) and immunohistochemistry, we show that IGF2 is highly expressed in both proliferating and involuting phase hemangioma, but is not detectable i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 34 publications
0
27
0
Order By: Relevance
“…bm-MPCs have been shown to express high levels of IGF2 as compared to mature fibroblasts (Brendel et al, 2005). Previous studies have shown almost undetectable mRNA and protein levels of IGF2 in venous and lymphatic malformations, congenital hemangiomas, pyogenic granulomas, and hemangioendotheliomas Yu et al, 2004). Therefore, we believe that bm-MPCs represent the most ideal positive control cell type for IGF2 studies in hemangioma.…”
Section: Robust Expression Of Igfs In Hemangioma-derived Stem Cellsmentioning
confidence: 79%
See 1 more Smart Citation
“…bm-MPCs have been shown to express high levels of IGF2 as compared to mature fibroblasts (Brendel et al, 2005). Previous studies have shown almost undetectable mRNA and protein levels of IGF2 in venous and lymphatic malformations, congenital hemangiomas, pyogenic granulomas, and hemangioendotheliomas Yu et al, 2004). Therefore, we believe that bm-MPCs represent the most ideal positive control cell type for IGF2 studies in hemangioma.…”
Section: Robust Expression Of Igfs In Hemangioma-derived Stem Cellsmentioning
confidence: 79%
“…Recent studies have shown that the self-sustaining nature of embryonic stem cells is established via endogenous regulators such as fibroblast growth factors (FGF) and insulin-like growth factor-2 (IGF2) (Bendall et al, 2007). IGF2 has been reported to be highly expressed during the proliferating phase of hemangiomas Ritter et al, 2002Ritter et al, , 2003Yu et al, 2004) implicating a role of IGF2 in hemSC activity.…”
Section: Introductionmentioning
confidence: 99%
“…29 IGF-2 is known to play a role in the development of IHs. 30 Circulating endothelial progenitor cells have been identified as vascular stem cells with the capacity to contribute to postnatal vascular proliferation such as IHs. 31,32 A summary of the angiogenic factors putatively involved in IHs and ROP is shown in Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Positive immunohistochemical staining for GLUT1 reliably distinguishes IH in all its phases from CH, which are almost uniformly negative [4,8,9]. Similarly, IGF2 (the insulinlike growth factor 2 gene) is highly expressed in IH in its proliferative and involuting phases, but only weakly expressed in RICH and NICH [7,10,11]. These findings may be linked, since insulin-like growth factor 2 induces expression of hypoxia-induced factor 1α [12], which in turn increases levels of GLUT1 mRNA [13].…”
Section: Discussionmentioning
confidence: 99%